A novel fan-shaped ultrabroadband solar absorber using nickel-based plasmonic metasurfaces - Ammar Armghan; Khaled Aliqab; Meshari Alsharari (Scientific Reports)
Abstract Herein, a simplistic design of the nanostructured absorber with a fan-shaped unit cell employed in its construction. The design layout of the absorber inspires with a standard three layers configuration, with a top and bottom surfaces made of metals with an intermediate spacer sandwiched within them. The proposed fan-shaped absorber has the capability to attain high absorption bandwidth from 400 to 8000 nm with a single-layer and low-profile design architecture. The absorption mechanism is primarily attributed to localized surface plasmon resonances at the edges of the elliptical resonators. A detailed sensitivity analysis has been inspected to observe the impact of various design parameters of the absorber. This design presents the flexibility in simplifying the existing absorber design while utilizing simple and straightforward unit-cell of the metal Nickel. It also presents stable absorption performance even at oblique incidence angles, considering both (TE & TM) waves polarization. This kind of nanostructured absorber can have a possible application in solar photovoltaics and thermal emission.